Photophysical studies of graphene quantum dots - Pyrene-derivatized porphyrins conjugates when encapsulated within Pluronic F127 micelles. (January 2018) - Managa, Muthumuni; Achadu, Ojodomo J.; Nyokong, Tebello
Abstract: Pyrene-derivatized H2, GaCl, and Zn porphyrins were immobilized on graphene quantum dots (GQDs) to form (GQDs-H2 TPrP, GQDs-GaClTPrP, and GQDs-ZnTPrP) conjugates through the π-π stacking interaction method followed by encapsulating into Pluronic F127 micelles to form (GQDs-H2 TPrP + F127, GQDs-GaClTPrP + F127, and GQDs-ZnTPrP + F127). Spectroscopic evidence shows that the resultant conjugates were stable due to the strong π-π stacking interaction between the GQDs and the porphyrins. The fluorescence and singlet oxygen generating behaviour of the porphyrins were investigated following incorporation. GQDs-GaClTPrP + F127 showed highest values of the binding constant (Kb ). The Stern-Volmer constant (Ksv ) for GQDs-ZnTPrP + F127 were the highest compared to other porphyrins derivatives. Highlights: Pyrene-derivatized H2, GaCl, and Zn porphyrins were immobilized on graphene quantum dots (GQDs). The conjugates were encapsulated into Pluronic F127 micelles resulting in water solubility. Singlet oxygen quantum yields increase in the presence of GQDs.